Determination of Sudan II dye in ethanol fuel by chromatographic and electroanalytical methods - Trindade, Magno Aparecido Gonçalves; Romanini, Daiane Cristina [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (My University, 2012)
Chromatographic and electroanalytical methods were developed to detect and quantify Sudan II (SD-II) dye in fuel ethanol samples. Sudan II is reduced at +0.50 V vs. Ag/AgCl on a glassy carbon electrode using Britton-Robinson buffer (pH 4.0) and N,N-dimethylformamide (70:30, v/v) + sodium dioctyl sulfosuccinate surfactant as supporting electrolyte, due to the azo group. This is the basis for its determination by square-wave voltammetry (SWV). Using the optimized conditions, it is possible to get a linear calibration curve from 3.00×10-6 to 1.80×10-5 mol L-1 (r = 0.998) with limits of detection (LOD) and quantification (LOQ) of 2.05×10-6 and 6.76×10-6 mol L-1, respectively. In addition, the hydroxyl substituent in the SD-II dye is also oxidized at +0.85 V vs. Ag/AgCl, which was conveniently used for its determination by high-performance liquid chromatography coupled to electrochemical detection (HPLC-ED). Under the optimized condition, the SD-II dye was eluted and separated using a reversed-phase column (cyanopropyl, CN) using isocratic elution with the mobile phase containing acetonitrile and aqueous lithium chloride (5.00×10-4 mol L-1) at 70:30 (v/v) and a flow rate of 1.2 mL min-1. Linear calibration curves were obtained from 3.00×10-7 to 2.00×10-6 mol L-1 (r = 0.999) with LOD and LOQ of 3.10×10-8 and 1.05×10-7 mol L-1, respectively. Both methods were simple, fast and suitable to detect and quantify the dye in fuel ethanol samples at recovery values between 83.0 to 102% (SWV) and 88.0 to 112% (HPLC-ED) with satisfactory precision and accuracy.
Keywords: Dye marker; Electroanalysis; Fuel analysis; HPLC-ED; Sudan II